Tests of Parameters Instability: Theoretical Study and Empirical Applications on Two Types of Models (ARMA Model and Market Model) - FARHANI, Sahbi (International Journal of Economics and Financial Issues, 2012)
This paper considers tests of parameters instability and structural change with known, unknown or multiple breakpoints. The results apply to a wide class of parametric models that are suitable for estimation by strong rules for detecting the number of breaks in a time series. For that, we use Chow, CUSUM, CUSUM of squares, Wald, likelihood ratio and Lagrange multiplier tests. Each test implicitly uses an estimate of a change point. We conclude with an empirical analysis on two different models (ARMA model and simple linear regression model). Keywords: Tests of parameters instability; Structural change; Breakpoints; ARMA model; SLRM. JEL Classifications: C22; G12; Q43